Pentingnya Menerapkan Protokol Kesehatan 5M Di TPA Asiyah Pamulang Timur - Qodaryanti, Lailatul Dwi; Ariyanti, Agustini Tri; Riana, Dini; Nurhaliza, Frida; Sumiar, Mochamad Yahya Cahya (Universitas Pamulang, 2021)
Community service is an activity that aims to help certain communities in several activities and develop community capabilities. Student service to the community regarding the spread and prevention of Covid-19 to increase public understanding, especially children at TPA Asiyah. In severe cases of COVID-19, it can cause pneumonia, acute respiratory syndrome, kidney failure, and even death. The purpose of the service is to find out how to prevent Covid-19 in the Community. The method used is a variety of lectures. This method was chosen to convey important concepts for training participants to understand and master, and the evaluation method was used to determine participants' understanding of the spread and prevention of Covid-19 in the surrounding community. Evaluation of the results of this service is carried out according to the percentage of community attendance, especially TPA Asiyah Children, understanding and results of activities. From these results obtained satisfactory results, the children at the Asiyah Pamulang Timur TPA have a high enthusiasm for this activity because they get additional knowledge about the spread and prevention of Covid-19 with the 5M movement. The conclusion is the application of how to prevent the spread of COVID-19 in everyday life. COVID-19 is a virus that damages the respiratory system and can cause several complications from infection to death. Suggestions from PKM activities. Based on the community service activities that we have carried out, we provide suggestions for readers to always maintain health during this Covid pandemic. This activity is expected to be useful for participants. Thus I can convey in this report, if there are shortcomings, we as authors apologize profusely. Keywords: Coronavirus; Protocol; 5M